CINEMA AS AN INSTRUMENT OF HISTORICAL REINTERPRETATION IN PERIODS OF DEMOCRATIC TRANSITIONS - Porras Ferreyra, Jaime (2013)
The following article studies the use of cinema as an instrument of ideas in a specific context, in this case, its role in democratic transitions with the objective to present to the citizens a historical reinterpretation in order to dispute the current views of the official history of the authoritarian regimes. To demonstrate this, the political character of motion pictures from Spain and Mexico during the political-institutional transformation will be analyzed. Factors like the demystification of some historical events, the screen presence of political actors traditionally ignored and the critique of certain values linked to authoritarianism become examples of the capacity of the seventh art as a space of political action.